Over fishing -a study with reference to the ring seine fishery - Edwin, Leela; Hridayanathan, C (Indian Journal of Fisheries, 2011)
The problem of overfishing along the inshore waters of Kerala has been reported to be aggravated by the introduction of the ring seines. In the context of indiscriminate proliferation and use of ring seines this study is made with reference to the changes in the species composition, length of important species and biomass landed. The data for this study were collected from Ambalapuzha and Cochin, two major centres of ring seine activity of the state. The species selected for this investigation were makerel, oil sardine and other sardines. The results of the study show the likelihood of overfishing in the ring seine fishery